Immunophenotypic Profiling of Erythroid Progenitor-Derived Extracellular Vesicles in Diamond-Blackfan Anaemia: A New Diagnostic Strategy. - Serena Macrì; Elisa Pavesi; Rossella Crescitelli; Anna Aspesi; Claudia Vizziello; Carlotta Botto; Paola Corti; Paola Quarello; Patrizia Notari; Ugo Ramenghi; Steven Robert Ellis; Irma Dianzani (PLoS ONE)
Diamond-Blackfan Anaemia (DBA) is a rare inherited anaemia caused by heterozygous mutations in one of 13 ribosomal protein genes. Erythroid progenitors (BFU-E and CFU-E) in bone marrow (BM) show a proapoptotic phenotype. Suspicion of DBA is reached after exclusion of other forms of BM failure syndromes. To improve DBA diagnosis, which is confirmed by mutation analysis, we tested a new approach based on the study of extracellular vesicles (EVs) isolated from plasma by differential centrifugations and analysed by flow cytometry. We chose CD34, CD71 and CD235a markers to study erythroid EVs. We characterised the EVs immunophentoypic profiles of 13 DBA patients, 22 healthy controls and 16 patients with other haematological diseases. Among the three EVs clusters we found, only the CD34+/CD71low population showed statistically significant differences between DBA patients and controls (p< 0.05). The absence of this cluster is in agreement with the low levels of BFU-E found in DBA patients. The assessment of ROC curves demonstrated the potential diagnostic value of this population. We suggest that this assay may be useful to improve DBA diagnosis as a quicker and less invasive alternative to BM BFU-E culture analysis.